Research Progress and Hotspot of Information Retrieval Correlation based on CiteSpace (Journal of Global Humanities and Social Sciences, 2025)
Taking 1760 journal papers of information retrieval relevance in the core database of Web of Science as the research object, using literature co-citation network and keyword co-occurrence network analysis, with information visualization as the means, this paper summarizes the research on the relevance of information retrieval. It is found that the current information retrieval correlation research network is concentrated, which is mainly divided into two main knowledge groups, retrieval algorithm and correlation cognition, with few frontier branches. And the knowledge fusion between the two groups needs to be strengthened. Since the emergence of natural language processing, information retrieval relevance has been improved along the path of natural language processing-machine learning-deep learning.